POTENSI EKSTRAK RIMPANG KUNYIT (Curcuma longa L.) TERHADAP PENYEMBUHAN LUKA PADA STUDI IN VIVO SYSTEMATIC REVIEW - Nadya Natasha (2023)
A wound is a condition in which tissue damage results from a break in the tissue's continuity. Due to increased rate of injuries causes the need to discover effective and efficient wound management. Currently, several studies have shown that Curcuma longa or turmeric extract has the potential to contribute in wound healing. This research goals is to present publications regarding the potential of turmeric (C. longa L.) rhizome extract on wound healing in vivo studies in order to prepare it for future usage as a herbal remedy for wound treatment. Methods: Systematic review by using Google Scholar and PubMed to search the literature on C. longa's role in wound healing. Search of the literature was carried out by using the PRISMA-P 2020 method and article exclusion was carried out using the Joanna Briggs Institute Critical Appraisal Checklist. Results: Founded 7 articles in the good category that conclude C.longa contributes to the wound healing progress through different mechanisms that affecting wound healing phase. Conclusion: In vivo investigations have shown that curcuma longa is capable to significantly affect the wound healing process. Keywords: Curcuma longa linn, extract, wound healing